Essential role of METTL3-mediated m 6 A modification in glioma stem-like cells maintenance and radioresistance - Visvanathan, A; Patil, V; Arora, A; Hegde, A S; Arivazhagan, A; Santosh, V; Somasundaram, K (Oncogene, 2018)
Despite advances in biology and therapeutic modalities, existence of highly tumorigenic glioma stem-like cells (GSCs) makes glioblastomas (GBMs) invincible. N6-methyl adenosine (m A), one of the abundant mRNA modifications catalyzed by methyltransferase-like 3 and 14 (METTL3/14), influences various events in RNA metabolism. Here, we report the crucial role of METTL3-mediated m A modification in GSC (neurosphere) maintenance and dedifferentiation of glioma cells. METTL3 expression is elevated in GSC and attenuated during differentiation. RNA immunoprecipitation studies identified SOX2 as a bonafide m A target of METTL3 and the m A modification of SOX2 mRNA by METTL3 enhanced its stability. The exogenous overexpression of 3'UTR-less SOX2 significantly alleviated the inhibition of neurosphere formation observed in METTL3 silenced GSCs. METTL3 binding and m A modification in vivo required intact three METTL3/m A sites present in the SOX2-3'UTR. Further, we found that the recruitment of Human antigen R (HuR) to m A-modified RNA is essential for SOX2 mRNA stabilization by METTL3. In addition, we found a preferential binding by HuR to the m6A-modified transcripts globally. METTL3 silenced GSCs showed enhanced sensitivity to γ-irradiation and reduced DNA repair as evidenced from the accumulation of γ-H2AX. Exogenous overexpression of 3'UTR-less SOX2 in METTL3 silenced GSCs showed efficient DNA repair and also resulted in the significant rescue of neurosphere formation from METTL3 silencing induced radiosensitivity. Silencing METTL3 inhibited RasV12 mediated transformation of mouse immortalized astrocytes. GBM tumors have elevated levels of METTL3 transcripts and silencing METTL3 in U87/TIC inhibited tumor growth in an intracranial orthotopic mouse model with prolonged mice survival. METTL3 transcript levels predicted poor survival in GBMs which are enriched for GSC-specific signature. Thus our study reports the importance of m A modification in GSCs and uncovers METTL3 as a potential molecular target in GBM therapy.